2019
DOI: 10.1186/s12889-019-7062-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between frailty and the combination of physical activity level and sedentary behavior in older adults

Abstract: Background The combined association of physical activity and sedentary behavior with adverse health factors is not yet clear in the literature. A combined analysis of physical activity level and sedentary behavior may provide evidence of the interrelation between these behavioral variables and the frailty syndrome. Thus, the aim of this study was to examine the relationship between physical activity level, sedentary behavior and frailty in older adults. Methods In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
84
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 38 publications
4
84
0
5
Order By: Relevance
“…Previous studies have suggested that current nonsmoking (including never and ex-smokers) [ 16 ], moderate to vigorous physical activity [ 17 , 18 ], moderate alcohol intake [ 22 , 23 ], and good dietary patterns [ 20 , 21 ] are associated with lower risk of frailty. To our knowledge, most previous studies examined one behavior at a time, some of which took into account smoking and, to a lesser extent, alcohol consumption but did not adjust for other health behaviors, despite known clustering of behaviors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that current nonsmoking (including never and ex-smokers) [ 16 ], moderate to vigorous physical activity [ 17 , 18 ], moderate alcohol intake [ 22 , 23 ], and good dietary patterns [ 20 , 21 ] are associated with lower risk of frailty. To our knowledge, most previous studies examined one behavior at a time, some of which took into account smoking and, to a lesser extent, alcohol consumption but did not adjust for other health behaviors, despite known clustering of behaviors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to intensity, some authors have shown that improvement in functional capacity takes place both in the practice of moderate activity and in the practice of high activity [18,36]. In this regard, some studies [37] have also refuted that the practice of low physical activity is ineffective for the functional improvement of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, insufficient PA and sedentary behavior have been associated with frailty. 8 To minimize the risk for these untoward outcomes, patients should be encouraged to maintain PA levels if at all possible while adhering to the social distancing constraints imposed by the pandemic.…”
Section: Discussionmentioning
confidence: 99%